The Effect of Job Placement, Human Capital, and Teamwork on Employee Performance at PT. Faithfull The Brand Kuta (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
Job placement is a brief and concise summary of the process of placing employees in positions that match their expertise, skills, and knowledge within an organization. Human capital refers to the knowledge, skills, competencies, and attributes of individuals that contribute to economic and social performance. Teamwork is one of the important factors in increasing effectiveness and productivity in an organizational environment. Employee performance is one of the main indicators in determining the success and competitiveness of an organization. This study aims to analyze the effect of job placement, human capital, and teamwork on employee performance at PT. Faithfull The Brand. This study was conducted at PT. Faithfull The Brand. The research population was employees of PT. Faithfull The Brand. The sample in this study was 87 respondents who were determined based on the Slovin formula. The data analysis technique used was multiple linear regression analysis using the SPSS program. The results of testing the hypothesis stated that job placement had a positive and significant effect on employee performance at PT. Faithfull The Brand, human capital had a positive and significant effect on employee performance at PT. Faithfull The Brand, and teamwork had a positive and significant effect on employee performance at PT. Faithfull The Brand.